2017
DOI: 10.1080/0020739x.2017.1352045
|View full text |Cite
|
Sign up to set email alerts
|

Inquiry as an entry point to equity in the classroom

Abstract: Although many policy documents include equity as part of mathematics education standards and principles, researchers continue to explore means by which equity might be supported in classrooms and at the institutional level. Teaching practices that include opportunities for students to engage in active learning have been proposed to address equity. In this paper, through aligning some characteristics of inquiry put forth by Cook, Murphy and Fukawa-Connelly with Gutiérrez's dimensions of equity, we theoretically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…Active learning helps with equity issues Led by Prof. Linda Columbus, our general chemistry classes started implementing active learning to address equity issues of higher failure and withdrawal rates among first-generation students and underrepresented minorities [9][10][11]. In the classroom, active learning helped eliminate those gaps by boosting achievement of vulnerable groups.…”
Section: Benefitsmentioning
confidence: 99%
“…Active learning helps with equity issues Led by Prof. Linda Columbus, our general chemistry classes started implementing active learning to address equity issues of higher failure and withdrawal rates among first-generation students and underrepresented minorities [9][10][11]. In the classroom, active learning helped eliminate those gaps by boosting achievement of vulnerable groups.…”
Section: Benefitsmentioning
confidence: 99%
“…Brown, Tang, and Hollman (2014), citing Brown (2009), stated that "part of [support groups'] strength lies in their empowering nature, where participants help each other as equals rather than taking on dependency roles where they rely on the advice of professionals" (p. 84). Therefore, in addition to inquiry-based mathematics education, demonstrations of productive failures may help shift power to create a more equitable classroom (Tang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It's a thermodynamic quantity with symbols and mathematical formulae to express it. Heat, according to Tang and Tan (Tang, 2017), is described as "a network of semantic meanings constructed across many representation modalities." Previous research (Paik,2007;Pelinek, 2021) showed that young children struggled to make semantic connections between various scientific topics.…”
Section: B Statement Of the Problemmentioning
confidence: 99%